Economic Disparities and Syphilis Incidence in Massachusetts, 2001-2013. (May 2017) - Smock, Laura; Caten, Evan; Hsu, Katherine; DeMaria, Alfred
Objectives: We used area-level indicators of poverty to describe economic disparities in the incidence rate of infectious syphilis in Massachusetts to (1) determine whether methods developed in earlier AIDS analyses in Massachusetts could be applied to syphilis and (2) characterize syphilis trends during a time of increased rates of syphilis incidence. Methods: Using census tract data and population counts from the US Census Bureau and Massachusetts data on syphilis, we analyzed the incidence rate of syphilis infection from 2001 to 2013 by the poverty level of the census tract in which people with syphilis resided, stratified by age, sex, and race/ethnicity. Results: The syphilis incidence rate increased in all census tract groups in Massachusetts from 2001 to 2013, and disparities in incidence rates by area poverty level persisted over time. The overall incidence rate of syphilis increased 6.9-fold from 2001 to 2013 in all census tract poverty-level groupings (from 1.5 to 10.3 per 100 000 population), but the rise in rate was especially high in the poorest census tracts (from 5.6 to 31.0 per 100 000 population) and among men (from 2.2 to 19.4 per 100 000 population). The highest syphilis incidence rate was among non-Hispanic black people. The largest changes in incidence rate occurred after 2010. One region had a disproportionate increase in incidence rates and a disproportionate impact on the statewide trend. Conclusions: Census tract poverty analyses can inform the targeting of interventions that make progress toward reducing disparities in rates of syphilis incidence possible.